Developmental care from theory to action - soleimani, farin; Sajedi, Ferozeh; Tork Zahrani, Shahnaz (Advances in Nursing & Midwifery, 2015)
Developmental care from theory to action Soleimani Farin. ( M.D)1 , Sajedi Ferozeh2 (M.D) Torkzahrani Shahnaz3 (M.Sc) 1. MD, Pediatrician, Associate Professor Pediatric Neurorehabilitation Research Center, University of Social Welfare and Rehabilitation Scienc-es, Tehran, Iran.2. MD, Pediatrician, Associate Professor Pediatric Neurorehabilitation Research Center, University of Social Welfare and Rehabilitation Scienc-es, Tehran, Iran.3. M.Sc. in Midwifery, Faculty member of Shahid Beheshti Medical University, Ph.D. Candidate Pediatric, Neurorehabilitation Research Center, Corresponding author: Torkzahrani Shahnaz; zahranishahnaz@yahoo.com Abstract Background: The premature or low birth weight infants in the neonatal intensive care unit admission are affected not only by body’s physiology and immature developmental condition but also by environmental stress; thereby they are at high risk of developing neurodevelopmental delay. The aim of this study was to review the emerging fi eld of neurodevelopmetal disorders and strategies to reduce it. Materials and Methods: In this review article, Iranmedex، Sciencedirect،google Scholar، SID, PubMed, Scopus, and EBSCO-CINAHL databases between 1960 to 2013 were searched for finding the relevant studies. Result: The review of literature indicates that developmental care mostly reports positive effects on neurodevelopmental outcomes and helps preterm infants cope with the environment of Neonatal Intensive Care Unit (NICU). Healing environment, partnering with families, positioning and handling, safeguarding sleep and optimizing nutrition are main core measures of developmental care. The structuring and designing of NICU environment for the high risk neonate has important policy implications for neonatal healthcare and beyond hospital stay. Key Words: Developmental care, Neurodevelopment, NICU, preterm, low birth weight,